Upaya Kepolisian dalam Penanganan Kasus Tindak Pidana Pembunuhan yang Dilakukan Warga Negara Asing (WNA ) terhadap Warga Negara Indonesia (WNI ) - Cokorda Gede Agung Rama Yudha; Anak Agung Sagung Laksmi Dewi; I Nyoman Sutama (Jurnal Konstruksi Hukum, 2021)
Police efforts in handling cases of murder committed by foreigners against Indonesian citizens based on article 338 of the Indonesian Criminal Code, where the action is an act of eliminating the life of another person, the police have the authority to handle the case as an investigator to maintain security and order in Indonesia. This study aims to analyze the investigation process and find out the settlement of the Criminal Act of Murder by foreigners against Indonesian citizens based on the judicial system in Indonesia reviewed with the Territorial Principle. This study uses the normative legal method. The results of the analysis show that the police have the authority as an investigator in cases of murder committed by foreigners against Indonesian citizens. The investigation process is carried out in accordance with the provisions of the Republic of Indonesia police regulation number 6 of 2019 and also article 6 of the Criminal Procedure Code regarding the provisions of article 2 of the Criminal Code which explains that the regulations in Indonesia apply to all citizens residing in Indonesia and enforcement is carried out against the perpetrators of murder tried in accordance with the judicial system in Indonesia based on the provisions of article 2 of the Criminal Code concerning the principle of territoriality with article 338 of the Criminal Code. Through this research, it is hoped that Indonesian citizens and foreigners will remain subject to the law. Furthermore, the government should pay attention to local residents who occupy Indonesian territory by reinforcing the applicable regulations in Indonesia.